1987
DOI: 10.1139/x87-004
|View full text |Cite
|
Sign up to set email alerts
|

A moisture strain index for loblolly pine

Abstract: Seedlings of Pinustaeda L. were planted in 1982 on a clear-cut site in the northeastern Piedmont of North Carolina. Two intensities of site preparation (chopping and shear–pile–disk) were applied in the previous year, and seedlings were maintained under three intensities of cultural practice (no treatment, application of herbicides, and hand weeding) for control of successional vegetation regrowth. Both site preparation and cultural practice significantly affected pine performance (relative growth rate) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Decreased predawn pine xylem pressure potential has been previously reported from experiments in which vegetation was removed from young pine stands (Nelson et al 1981, Carter et al 1984, Byrne et al 1987.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Decreased predawn pine xylem pressure potential has been previously reported from experiments in which vegetation was removed from young pine stands (Nelson et al 1981, Carter et al 1984, Byrne et al 1987.…”
Section: Discussionmentioning
confidence: 59%
“…Decreased predawn pine xylem pressure potential has been previously reported from experiments in which vegetation was removed from young pine stands (Nel-son et al 1981, Carteret al 1984, Byrne et al 1987. Although these studies suggested that herbaceous plants (Nelson et al 1981) or hardwood and herbaceous plants strongly compete with pine for soil moisture (Carteret al 1984, Byrne et al 1987, none of these reports provide a satisfactory means for accounting for temporal variation in pine water potential. Schulze et al ( 1980a, b) and Linder et al ( 198 7) calculated a parameter termed "deficit-time."…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there is an abundance of information relating loblolly pine response to the amount of competing herbaceous and (or) woody plants, the underlying causes or mechanisms for such responses are less well understood. A number of studies have shown soil water to increase and water stress of loblolly pine seedlings to be lessened,in the absence of woody and (or) herbaceous vegetation (Nelson et al 1981;Miller et al 1987;Byrne et al 1987. Perry et al 1994.…”
Section: Introductionmentioning
confidence: 99%
“…There have been limited attempts to integrate water deficit over time and relate it to tree growth, for example "moisture strain index" (Byrne et al, 1987).…”
Section: Integration Of Stress Factorsmentioning
confidence: 99%